1995
DOI: 10.1111/j.1365-2591.1995.tb00302.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an Nd–YAG pulsed laser on the cleaning of the root canal and the formation of a fused apical plug

Abstract: A Neodymium-yttrium aluminium garnet (Nd-YAG) pulsed laser was used in vitro to determine whether various laser energy levels from 0.75 W to 1.7 W at 15 pulses s(-1) (pps) were able to (i) remove debris from the walls of prepared root canals (ii) remove pulpal tissue from unprepared canals and (iii) create a fused apical plug from dentine chips, hydroxyapatite (HAP) or low-fusing dental porcelain. Single-rooted teeth were sectioned at the amelocemental junction and the crowns discarded. The root canals of 50 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Although scaling and root planning remain the initial treatment modalities in periodontal therapy, the use of a softtissue diode laser can be considered as an efficacious adjunct to conventional periodontal therapy. The role of laser radiation in disinfection of the root canal has been demonstrated by Shetty et al, [11] Saunders et al [12] Yamazaki et al, [13] and Takeda et al [14] The use of a diode laser in soft-tissue procedures are advocated because it helps in bacterial decontamination, promotes reestablishment of connective tissue attachment and are less invasive nature, which reduces post-operative swelling. [15,16] CONCLUSION Based on the above study it can be concluded that endoperio lesions always possess a challenge to the clinician for correct diagnosis and treatment planning.…”
Section: Discussionmentioning
confidence: 98%
“…Although scaling and root planning remain the initial treatment modalities in periodontal therapy, the use of a softtissue diode laser can be considered as an efficacious adjunct to conventional periodontal therapy. The role of laser radiation in disinfection of the root canal has been demonstrated by Shetty et al, [11] Saunders et al [12] Yamazaki et al, [13] and Takeda et al [14] The use of a diode laser in soft-tissue procedures are advocated because it helps in bacterial decontamination, promotes reestablishment of connective tissue attachment and are less invasive nature, which reduces post-operative swelling. [15,16] CONCLUSION Based on the above study it can be concluded that endoperio lesions always possess a challenge to the clinician for correct diagnosis and treatment planning.…”
Section: Discussionmentioning
confidence: 98%
“…Saunders et al 9 and Khan et al 3 believe that an advantage Nd:YAG laser is the fact that the opic fiber to be flexible, that allows an easy penetration in the root canal, also in areas with difficult access as the apical third. However, it was verified in the present study that laser action inside the root canal is limited.…”
Section: Nd:yag Laser Irradiation and Root Canal Dentin Wall 403mentioning
confidence: 99%
“…On the other hand, Saunders et al, 9 in 1995, verified that smear layer and debris removal from root canal after Nd:YAG laser application was not effective when compared with smear layer removal promoted by conventional preparation. According to this author, it was not possible to observe where there was the removal of smear layer and where there was not, because both situation presented similar aspects in the scanning electron microscopic.…”
Section: Nd:yag Laser Irradiation and Root Canal Dentin Wall 403mentioning
confidence: 99%
See 1 more Smart Citation
“…Dederich et al 1 suggest the Nd: YAG laser irradiation reduces the permeability of the dentin wall in root canal due to the melting of the tissue. Marques et al 5 showed the pulsed Nd:YAG laser has the ability of melting the dentin wall in a root canal using an output of 1 to 3 W. On the other hand, Saunders et al 6 had reported that pulsed Nd:YAG laser irradiation with a power of 0.75 to 1.7 W did not melt the wall of the root canal and failed to remove the debris.…”
Section: Introductionmentioning
confidence: 99%